(untitled) (International Journal of Medical and Surgical Sciences, 2015)
Spermatogenesis is a series of events that constitute programmed cell differentiation, with dramatic changes in morphology, biochemistry and gene expression which are regulated by temporal and especially endocrine, paracrine and autocrine mechanisms. During the various stages of spermatogenesis and particularly during the differentiation of spermatids, there is massive degradation of cytosolic proteins, nuclear and membrane due to the elimination of much of the cytoplasm which has round spermatid. This protein degradation occurs within the seminiferous epithelium and is mediated by cellular systems described for this purpose. The proteasome is a multienzyme complex responsible for degrading the majority of nuclear and cytosolic proteins, after they are marked for destruction by covalent attachment of ubiquitin molecules. This selective destruction of cellular proteins is a key mechanism in the process of spermatogenesis. This article discusses the basics of male gonadal physiological process and the current understanding of the role of the ubiquitin proteasome system in the functional maintenance of spermatogenesis are reviewed.